2015
DOI: 10.1155/2015/810376
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Phosphodiesterase‐5 Inhibitor Therapy for Portopulmonary Hypertension

Abstract: Phosphodiesterase-5 inhibitor therapy improved hemodynamics and functional class at six months in a cohort of patients with portopulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Small case series suggest that sildenafil improves functional capacity and increases cardiac output. [576][577][578] It should be noted that sildenafil can precipitate variceal bleeding and as such, caution should be exercised. 579 Prostacyclin analogues.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Small case series suggest that sildenafil improves functional capacity and increases cardiac output. [576][577][578] It should be noted that sildenafil can precipitate variceal bleeding and as such, caution should be exercised. 579 Prostacyclin analogues.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…There are limited data evaluating the long-term survival of patients with PPH managed with medical therapy alone. Recent study from UK showed that phosphodiesterase 5 inhibitors were the most frequently used targeted therapy (63%) followed by prostacyclin analogs (12.7%), and endothelin receptor antagonists (10%) [32].…”
Section: Treatmentmentioning
confidence: 99%
“…Phosphodiesterase-5 inhibitor therapy is efficacious in other causes of WHO group I pulmonary arterial hypertension [32]. They inhibit the growth of pulmonary vascular smooth muscle cells and lower mean pulmonary artery pressure and pulmonary vascular resistance by mediating vasodilation through guanosine monophosphate [2,27].…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both drugs appear to be well tolerated in POPH and do not adversely affect hepatic function. In the large Canadian sildenafil series (n = 20 POPH), treatment was successful (PVR decreased by a mean of -236 dynes.s.cm -5 at 6 months) and the drug was used in 2 patients with increased pulmonary artery wedge pressure (PAWP), but their outcome data was not reported 51 .…”
Section: Pde-5 Inhibitionmentioning
confidence: 99%